Inhalation treatment for asthma. Issue 1 (January 1986) - Reiser, J; Warner, J O
Abstract : Inhaled medication has revolutionised the lives of many children with asthma. Despite this we see many children for whom appropriate inhaled medication has been prescribed but whose symptoms continue to be poorly controlled. In our experience this is often due to poor technique or inappropriately prescribed devices and an inadequate understanding of when and how to use the treatment. The prescribing physician must have a clear idea of the optimal inhalation technique. We have reviewed the standard devices available and our use of them in the treatment of childhood asthma.